EFEKTIVITAS PENYUSUNAN RENCANA KEGIATAN DAN ANGGARAN SEKOLAH PROGRAM BANTUAN OPERASIONAL SEKOLAH (BOS) DI UPT SATUAN PENDIDIKAN SEKOLAH DASAR NEGERI PURWODADI III - Ardianto Ramadhani; Khumaidi (Journal Multicultural of Islamic Education, 2021)
This study aims to explain the effectiveness of the implementation of the BOS program in planning activities, namely the preparation of school activity plans and budgets (RKAS) in the UPT education unit of the Purwodadi III Public Elementary School. This research is based on the fact that the implementation of the BOS program can be effective when the RKAS is compiled and determined jointly by the school management team, teachers and school committee. This research is a qualitative descriptive study, where data is collected through observation, interviews and document collection. Then analyzed with an interactive model. To further strengthen the results of this study a triangulation model is used.